Electrolytes and batteries
Patent Information
- Application Number
- CN202611352964.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-02
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]然而,锂离子电池在低温环境下的性能衰减问题一直是制约其广泛应用的关键瓶颈之一
本发明提出的电解液,通过各功能组分的协同作用,B系锂盐与S系锂盐与其它各组分的协同复配,实现了高低温性能的兼顾与统一。B系锂盐和S系锂盐在电解液中“空间分区、功能互补”,B系锂盐主要作用于正极界面,通过化学吸附形成富硼保护层以保障高温界面稳定性;S系锂盐主要作用于负极界面,通过优先还原形成富无机SEI膜,以提升低温去溶剂化动力学,两者互不干扰、协同增效,使电解液在-40℃至60℃的宽温区内均能保持优异的电化学性能。
Smart Images

Figure CN123018131A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of secondary battery technology, and in particular to an electrolyte and a battery. Background Technology
[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles, and energy storage systems due to their advantages such as high energy density, long cycle life, and no memory effect. With the continuous expansion of lithium battery applications, especially in extreme environments such as new energy vehicles, special equipment, aerospace, and deep-sea exploration, increasingly higher requirements are being placed on the comprehensive electrochemical performance of batteries over a wide temperature range (particularly from -40℃ ultra-low temperature to 60℃ high temperature).
[0003] However, the performance degradation of lithium-ion batteries at low temperatures has always been one of the key bottlenecks restricting their widespread application. The fundamental reason for this low-temperature performance degradation lies in the following: as the temperature decreases, the viscosity of the carbonate-based electrolyte increases significantly, and the ionic conductivity drops sharply. Simultaneously, the solid-phase diffusion coefficient of lithium ions within the active material decreases, and the charge transfer impedance increases significantly. Particularly at the negative electrode / electrolyte interface, the desolvation process of lithium ions becomes extremely difficult, leading to a severe deterioration in electrode reaction kinetics. At high temperatures (such as above 60°C), the electrolyte faces problems such as decreased thermal stability, intensified side reactions, and dissolution of transition metal ions, resulting in a significant decrease in battery cycle life and storage performance.
[0004] A more challenging aspect is that improving the low-temperature performance of electrolytes and improving their high-temperature performance are often mutually restrictive. For example, while increasing the proportion of low-viscosity, low-melting-point co-solvents in the electrolyte helps improve low-temperature performance, it often sacrifices the electrolyte's antioxidant stability and high-temperature interfacial stability. Therefore, how to design electrolyte components to improve low-temperature ion conductivity while ensuring high-temperature interfacial stability, thus achieving a comprehensive performance balance of the electrolyte over a wide temperature range, is a pressing technical challenge in the field of lithium-ion battery electrolytes. Summary of the Invention
[0005] The purpose of this invention is to overcome the above-mentioned technical deficiencies and to propose an electrolyte and a battery, aiming to provide an electrolyte that can take into account both the high-temperature and low-temperature performance of lithium-ion batteries.
[0006] To achieve the above-mentioned technical objectives, a first aspect of the present invention provides an electrolyte comprising a lithium salt, an organic solvent, and additives. The lithium salt comprises lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, B-series lithium salts, and S-series lithium salts, wherein the chemical formula of the B-series lithium salt is LiBF₂. n1 X m1 The chemical formula of the S-series lithium salt is Li. x SO n2 Fm2 X includes one or more of oxalate, sulfate, and catechol, n1=0~4, m1=0~2, x=1~2, n2=2~4, m2=0~1; the organic solvent includes ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate; the additive includes vinylene carbonate.
[0007] In some embodiments, based on the total mass of the electrolyte, the mass percentage of each component in the lithium salt is as follows: lithium hexafluorophosphate 3.5%~9%, lithium difluorosulfonyl imide 5%~13%, B-series lithium salt 0.1%~1.0%, and S-series lithium salt 0.1%~1.0%.
[0008] In some embodiments, the B-series lithium salt includes one or more of LiBF2C2O4, LiBF2SO4, LiB(C2O4)2, LiBF4, LiBF2(C6H4O2), LiB(C6H4O2)2, and LiB(C2O4)(C6H4O2); and / or, the S-series lithium salt includes one or more of LiSO3F, LiSO2F, Li2SO4, and Li2SO3.
[0009] In some embodiments, based on the total mass of the electrolyte, the mass percentage of each component in the organic solvent is: ethylene carbonate 20%~30%, dimethyl carbonate 10%~30%, diethyl carbonate 0%~20%, and methyl ethyl carbonate 15%~35%.
[0010] In some embodiments, based on the total mass of the electrolyte, the mass percentage of each component in the additive is: 0%~0.5% trifluorophenylphosphine, 0.5%~3% vinylene carbonate, and 0%~1% vinyl sulfate.
[0011] In some embodiments, based on the total mass of the electrolyte, the mass percentages of each component are as follows: lithium hexafluorophosphate 4.5%~5.5%, lithium difluorosulfonyl imide 8.0%~10.0%, B-series lithium salt 0.4%~0.8%, S-series lithium salt 0.2%~0.5%; ethylene carbonate 23%~27%, dimethyl carbonate 18%~22%, diethyl carbonate 6%~10%, methyl ethyl carbonate 23%~27%; trifluorophenylphosphine 0.15%~0.35%, vinylene carbonate 1.5%~2.5%, ethylene sulfate 0.3%~0.7%.
[0012] In some embodiments, based on the total mass of the electrolyte, the mass percentages of each component are as follows: lithium hexafluorophosphate 3.8%~4.6%, lithium difluorosulfonyl imide 10%~12%, B-series lithium salts 0.3%~0.7%, S-series lithium salts 0.2%~0.6%; ethylene carbonate 20%~24%, dimethyl carbonate 26%~30%, diethyl carbonate 0%~5%, methyl ethyl carbonate 30%~34%; trifluorophenylphosphine 0%~0.2%, vinylene carbonate 1.0%~2.0%, ethylene sulfate 0.4%~0.8%.
[0013] In some embodiments, based on the total mass of the electrolyte, the mass percentages of each component are as follows: lithium hexafluorophosphate 6.0%~7.0%, lithium difluorosulfonyl imide 6.0%~8.0%, B-series lithium salt 0.7%~1.0%, S-series lithium salt 0.1%~0.5%; ethylene carbonate 26%~30%, dimethyl carbonate 10%~14%, diethyl carbonate 16%~20%, methyl ethyl carbonate 16%~20%; trifluorophenylphosphine 0.2%~0.4%, vinylene carbonate 2.5%~3%, ethylene sulfate 0.7%~1%.
[0014] In a second aspect, the present invention provides a battery comprising the electrolyte described in the first aspect of the present invention.
[0015] In some embodiments, the positive electrode comprises a lithium iron phosphate-based positive electrode active material; and / or, the battery comprises a negative electrode comprising a graphite-based negative electrode active material.
[0016] Compared with the prior art, the beneficial effects of the present invention include: The electrolyte proposed in this invention achieves a balance and uniformity in high and low temperature performance through the synergistic effect of various functional components, including the synergistic combination of B-series lithium salts and S-series lithium salts with other components. The B-series and S-series lithium salts in the electrolyte exhibit "spatial partitioning and functional complementarity." The B-series lithium salt primarily acts at the positive electrode interface, forming a boron-rich protective layer through chemisorption to ensure high-temperature interface stability; the S-series lithium salt primarily acts at the negative electrode interface, preferentially reducing to form an inorganic SEI-rich film to enhance low-temperature desolvation kinetics. The two do not interfere with each other but work synergistically, enabling the electrolyte to maintain excellent electrochemical performance across a wide temperature range of -40℃ to 60℃. Attached Figure Description
[0017] Figure 1 These are cycle performance test graphs of the batteries in Examples 1-2 and Comparative Examples 1-2 of the present invention at 60°C 3C / 3C. Detailed Implementation
[0018] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.
[0019] In a first aspect, the present invention provides an electrolyte comprising a lithium salt, an organic solvent, and an additive, wherein the lithium salt comprises lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, B-series lithium salts, and S-series lithium salts, and the chemical formula of the B-series lithium salt is LiBF. n1 X m1 The chemical formula of the S-series lithium salt is Li. x SO n2 F m2 X includes one or more of oxalate, sulfate, and catechol, n1=0~4, m1=0~2, x=1~2, n2=2~4, m2=0~1; the organic solvent includes ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate; the additive includes vinylene carbonate.
[0020] Therefore, the electrolyte proposed in this invention, through the synergistic blending of B-series lithium salts and S-series lithium salts with other components, achieves a balance and unity in high and low temperature performance. The B-series and S-series lithium salts in the electrolyte exhibit "spatial partitioning and functional complementarity." The B-series lithium salt primarily acts at the positive electrode interface, forming a boron-rich protective layer through chemisorption to ensure high-temperature interface stability; the S-series lithium salt primarily acts at the negative electrode interface, preferentially reducing to form an inorganic-rich SEI film to enhance low-temperature desolvation kinetics. The two do not interfere with each other but work synergistically, enabling the electrolyte to maintain excellent electrochemical performance across a wide temperature range of -40℃ to 60℃.
[0021] Specifically, this invention introduces specific types of B-series lithium salts, utilizing the Lewis acidity of the electron-deficient boron centers in their molecular structure to effectively remove trace amounts of HF and H2O from the electrolyte and inhibit the hydrolysis of LiPF6. Simultaneously, the B-series lithium salts undergo chemisorption on the surface of the lithium iron phosphate cathode, forming a molecular-level interfacial protective layer rich in BO / BF species. This protective layer effectively complexes metal ions dissolved from the surface of the cathode active material, preventing metal shuttles to the anode and damaging the SEI film, thereby significantly improving the cycle stability of the electrolyte at high temperatures (60°C). By introducing specific types of S-series lithium salts, these salts preferentially decompose on the anode surface during the formation stage, generating an SEI film rich in inorganic components such as Li2SO3, Li2S2O4, and LiF. This SEI film exhibits high ionic conductivity and low lithium-ion desolvation activation energy (Ea), significantly reducing the lithium ion desolvation activation energy at low temperatures. + The desolvation energy barrier required to cross the SEI membrane effectively solves the capacity decay problem caused by the sharp increase in interfacial impedance at low temperatures in traditional carbonate-based electrolytes.
[0022] In some embodiments, preferably, n1, m1, n2, and m2 are all integers.
[0023] In some embodiments, based on the total mass of the electrolyte, the mass percentage of each component in the lithium salt is as follows: lithium hexafluorophosphate 3.5%~9%, lithium difluorosulfonyl imide 5%~13%, B-series lithium salt 0.1%~1.0%, and S-series lithium salt 0.1%~1.0%.
[0024] As an example, based on the total mass of the electrolyte, the mass percentage of lithium hexafluorophosphate (LiPF6) can be 3.5%, 4%, 5%, 6%, 7%, 8%, 9%, or any two of the above values; the mass percentage of lithium bisfluorosulfonylimide (LiFSI) can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, or any two of the above values; the mass percentage of B-series lithium salts can be 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.0%, or any two of the above values; and the mass percentage of S-series lithium salts can be 0.1%, 0.3%, 0.5%, 0.7%, 0.9%, 1.0%, or any two of the above values.
[0025] Therefore, when the mass content of B-series lithium salt is below 0.1%, the improvement in high-temperature cycle life is not significant; when the mass content exceeds 1.0%, excessive B-series lithium salt increases electrolyte viscosity and impairs low-temperature performance. The concentration range of 0.1% to 1.0% specified in this application represents the optimal window for the synergistic effect of B-series lithium salt with other components, achieving excellent overall high and low temperature performance while avoiding negative interactions between components.
[0026] When the mass content of S-based lithium salt is below 0.1%, the improvement in low-temperature conductivity is not significant; when the mass content exceeds 1.0%, excessive S-based lithium salt will increase interfacial impedance due to excessive film formation. The concentration range of 0.1% to 1.0% specified in this application represents the optimal window for the synergistic effect of S-based lithium salt and other components. While achieving excellent comprehensive performance at high and low temperatures, it avoids negative interactions between components, demonstrating the scientific and advanced nature of the formulation design in this invention.
[0027] In some embodiments, the B-series lithium salt includes one or more of LiBF2C2O4, LiBF2SO4, LiB(C2O4)2 (LiBOB), LiBF4, LiBF2(C6H4O2), LiB(C6H4O2)2, and LiB(C2O4)(C6H4O2). These B-series lithium salts contain electron-deficient boron centers and exhibit Lewis acidity, effectively removing trace amounts of HF and H2O from the electrolyte and inhibiting the hydrolysis of LiPF6. Simultaneously, the B-series lithium salt undergoes chemisorption on the surface of the lithium iron phosphate cathode, forming a molecular-level interfacial protective layer rich in BO / BF species. This protective layer effectively complexes metal ions dissolved from the surface of the positive electrode active material, preventing metal shuttles to the negative electrode and damaging the SEI film, thereby significantly improving the cycle stability of the electrolyte at high temperatures (60°C).
[0028] In some embodiments, the S-series lithium salt includes one or more of LiSO3F, LiSO2F, Li2SO4, and Li2SO3. These S-series lithium salts can preferentially decompose on the negative electrode surface during the formation stage, generating an SEI film rich in inorganic components such as Li2SO3, Li2S2O4, and LiF. This SEI film exhibits high ionic conductivity and low lithium-ion desolvation activation energy (Ea), significantly reducing the lithium ion desolvation activation energy at low temperatures. + The desolvation energy barrier required to cross the SEI membrane effectively solves the capacity decay problem caused by the sharp increase in interfacial impedance at low temperatures in traditional carbonate-based electrolytes.
[0029] In some embodiments, based on the total mass of the electrolyte, the mass percentage of each component in the organic solvent is as follows: ethylene carbonate (EC) 20%~30%, dimethyl carbonate (DMC) 10%~30%, diethyl carbonate (DEC) 0%~20%, and ethyl methyl carbonate (EMC) 15%~35%.
[0030] As an example, based on the total mass of the electrolyte, the mass percentage of ethylene carbonate can be 20%, 22%, 24%, 25%, 27%, 29%, 30%, or any two of the above values; the mass percentage of dimethyl carbonate can be 10%, 15%, 20%, 25%, 30%, or any two of the above values; the mass percentage of diethyl carbonate can be 0%, 5%, 10%, 15%, 20%, or any two of the above values; and the mass percentage of methyl ethyl carbonate can be 15%, 20%, 25%, 30%, 35%, or any two of the above values.
[0031] Therefore, by combining the above four organic solvents and adjusting the ratio of high dielectric constant solvent (EC) to low viscosity solvent (DMC, EMC), and introducing an appropriate amount of DEC, the dielectric constant, viscosity, and lithium-ion solvation structure of the electrolyte can be optimized, ensuring high ionic conductivity and low interfacial impedance over a wide temperature range.
[0032] In some embodiments, based on the total mass of the electrolyte, the mass percentage of each component in the additive is: trifluorophenylphosphine (TFPP) 0%~0.5%, vinylene carbonate (VC) 0.5%~3%, and vinyl sulfate (DTD) 0%~1%.
[0033] As an example, based on the total mass of the electrolyte, the mass percentage of trifluorophenylphosphine can be 0%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, or any two of the above values; the mass percentage of vinylene carbonate can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, or any two of the above values; and the mass percentage of vinyl sulfate can be 0%, 0.2%, 0.4%, 0.5%, 0.7%, 0.9%, 1%, or any two of the above values.
[0034] Therefore, the above three additives, combined with the aforementioned organic solvent and lithium salt, allow VC, as the main film-forming additive, to form a stable SEI film at the negative electrode; TFPP, as a high-temperature stabilizer, can scavenge free radicals in the electrolyte and suppress high-temperature side reactions; and DTD, as a sulfur-containing additive, can further optimize the composition of the SEI film and reduce interfacial impedance. The synergistic effect of these three additives can further improve the battery's cycle life and storage performance over a wide temperature range.
[0035] In some embodiments, based on the total mass of the electrolyte, the mass percentages of each component are as follows: lithium hexafluorophosphate 4.5%~5.5%, lithium difluorosulfonyl imide 8.0%~10.0%, B-series lithium salt 0.4%~0.8%, S-series lithium salt 0.2%~0.5%; ethylene carbonate 23%~27%, dimethyl carbonate 18%~22%, diethyl carbonate 6%~10%, methyl ethyl carbonate 23%~27%; trifluorophenylphosphine 0.15%~0.35%, vinylene carbonate 1.5%~2.5%, ethylene sulfate 0.3%~0.7%. Therefore, the electrolyte with the above proportions is more suitable for lithium-ion batteries with a wide temperature range, exhibiting high ionic conductivity at -40℃ and maintaining excellent cycle stability at 60℃, resulting in optimal overall performance.
[0036] Preferably, in the above electrolyte, the B-series lithium salt is a mixture of LiBF4 and LiBF2C2O4, and the S-series lithium salt is LiSO3F. Thus, LiBF4 provides stable BF4. -Anions help form a stable interfacial film; LiBF2C2O4 can form a protective layer rich in BO species on the positive electrode surface; and LiSO3F can be preferentially reduced at the negative electrode to form an SEI film rich in Li2SO3 and LiF. The combination of these three can simultaneously optimize the positive and negative electrode interfaces and maximize the synergistic effect.
[0037] In some embodiments, based on the total mass of the electrolyte, the mass percentages of each component are as follows: lithium hexafluorophosphate 3.8%~4.6%, lithium difluorosulfonyl imide 10%~12%, B-series lithium salts 0.3%~0.7%, S-series lithium salts 0.2%~0.6%; ethylene carbonate 20%~24%, dimethyl carbonate 26%~30%, diethyl carbonate 0%~5%, methyl ethyl carbonate 30%~34%; trifluorophenylphosphine 0%~0.2%, vinylene carbonate 1.0%~2.0%, ethylene sulfate 0.4%~0.8%. The electrolyte with the above proportions is more suitable for lithium-ion batteries with high low-temperature performance requirements. By increasing the proportion of low-viscosity, low-melting-point solvents (DMC, EMC) and combining it with a high content of LiFSI, the viscosity of the electrolyte at low temperatures can be significantly reduced, and the ionic conductivity improved. Simultaneously, the B-series and S-series lithium salts synergistically optimize the interface, ensuring rapid lithium-ion transport in the SEI film at low temperatures.
[0038] Preferably, in the electrolyte, the B-series lithium salt is LiBF2C2O4 and the S-series lithium salt is LiSO3F. Thus, LiBF2C2O4 forms a thin and dense protective layer on the positive electrode surface, and LiSO3F forms a low-resistance SEI film on the negative electrode. The two work together to ensure the interfacial transport dynamics at low temperatures and also take into account the interfacial stability at high temperatures.
[0039] In some embodiments, based on the total mass of the electrolyte, the mass percentages of each component are as follows: lithium hexafluorophosphate 6.0%~7.0%, lithium difluorosulfonyl imide 6.0%~8.0%, B-series lithium salt 0.7%~1.0%, S-series lithium salt 0.1%~0.5%; ethylene carbonate 26%~30%, dimethyl carbonate 10%~14%, diethyl carbonate 16%~20%, methyl ethyl carbonate 16%~20%; trifluorophenylphosphine 0.2%~0.4%, vinylene carbonate 2.5%~3%, ethylene sulfate 0.7%~1%. The electrolyte with the above proportions is more suitable for lithium-ion batteries with high high-temperature performance requirements. By increasing the ratio of EC and DEC and increasing the amount of VC and TFPP, the antioxidant stability and high-temperature interface stability of the electrolyte can be improved. Simultaneously, an appropriate amount of B-series lithium salt forms a stable protective layer on the positive electrode surface, significantly suppressing side reactions at high temperatures.
[0040] Preferably, in the above electrolyte, LiBOB is selected as the B-series lithium salt, and Li₂SO₄ is selected as the S-series lithium salt. Thus, LiBOB can simultaneously form a stable interfacial film on both the positive and negative electrodes. In particular, its decomposition products can form a cross-linked network rich in BO and BF on the positive electrode surface, effectively inhibiting the dissolution of metal ions from the positive electrode material at high temperatures. Li₂SO₄, as a film-forming additive, can further optimize the inorganic composition of the SEI film, improving its thermal stability and density. The synergistic effect of both significantly improves the battery's cycle life and storage performance at high temperatures.
[0041] In a second aspect, the present invention provides a battery comprising the electrolyte described in the first aspect. Thus, the battery proposed by the present invention exhibits excellent high-temperature and low-temperature performance, maintaining superior electrochemical performance over a wide temperature range of -40°C to 60°C.
[0042] In some embodiments, the battery may include a negative electrode, a positive electrode, an electrolyte, and a separator. The positive electrode, negative electrode, and separator are all immersed in the electrolyte. During the charging and discharging process of the battery, active lithium ions are inserted and extracted back and forth between the positive and negative electrode. The electrolyte plays the role of conducting ions between the positive and negative electrode. The separator is disposed between the positive and negative electrode and mainly plays the role of preventing short circuits between the positive and negative electrode, while allowing active lithium ions to pass through.
[0043] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer located at least on one side of the negative electrode sheet. The negative electrode active material layer may include a negative electrode active material, a negative electrode conductive agent, and a negative electrode binder.
[0044] In some embodiments, the negative current collector includes copper foil, composite copper foil, etc.
[0045] In some embodiments, the negative electrode active material may include carbon-based materials (such as artificial graphite), silicon-based materials, tin-based materials, etc.
[0046] In some embodiments, the battery includes a negative electrode sheet, which comprises a graphite-based negative electrode active material. Therefore, graphite exhibits greater stability compared to other negative electrode active materials. Combined with the electrolyte described above, it facilitates the preferential reduction and decomposition of S-based lithium salts on the graphite negative electrode surface during the formation stage, generating an SEI film rich in inorganic components such as Li₂SO₃, Li₂S₂O₄, and LiF. This SEI film possesses high ionic conductivity and a low lithium-ion desolvation activation energy (Ea), significantly reducing the desolvation energy barrier required for Li⁺ to cross the SEI film at low temperatures. This effectively solves the capacity decay problem caused by the sharp increase in interfacial impedance at low temperatures in traditional carbonate-based electrolytes.
[0047] In some embodiments, the negative electrode binder includes at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).
[0048] In some embodiments, the negative electrode conductive agent includes at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0049] Typically, a positive electrode sheet includes a positive current collector and a positive active material layer formed on at least one side of the positive current collector, wherein the positive active material layer includes a positive active material, a positive conductive agent, and a positive binder.
[0050] In some embodiments, the positive current collector can be a metal current collector or a composite current collector. Metal current collectors include at least one of aluminum foil current collectors and carbon-coated aluminum foil current collectors; composite current collectors may include a polymeric material substrate and a metal layer formed on at least one surface of the polymeric material substrate. Composite current collectors can be formed by forming a metal material (copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys, etc.) on a polymeric material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0051] In some embodiments, the positive electrode active materials for lithium-ion batteries mainly include layered oxides, spinel structure positive electrode active materials, olivine structure positive electrode active materials (lithium iron phosphate), and polyanionic positive electrode active materials.
[0052] In some embodiments, the positive electrode comprises a lithium iron phosphate-based positive electrode active material. Thus, in combination with the electrolyte, the B-series lithium salt more readily undergoes chemical adsorption on the surface of the lithium iron phosphate positive electrode, forming a molecular-level interfacial protective layer rich in BO / BF species. This protective layer can effectively complex Fe dissolved from the surface of the positive electrode material. 2+ Ions, preventing Fe 2+ The electrolyte shuttles to the negative electrode to disrupt the SEI film, thereby significantly improving the cycling stability of the electrolyte in a high-temperature (60°C) environment.
[0053] In some embodiments, the positive electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0054] In some embodiments, the diaphragm includes a polyethylene diaphragm, a polypropylene diaphragm, a polyethylene / polypropylene composite diaphragm, etc.
[0055] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0056] Example 1 Suitable for vehicle platforms that require low-temperature start-up and high-temperature fast charging, aiming for a balance of comprehensive electrochemical performance over a wide temperature range (-40℃~60℃).
[0057] Formula composition (all percentages by weight) (1) Lithium salts LiPF6: 5.0% LiFSI: 9% B-series lithium salts (using 0.3% each of LiBF4 and LiBF2C2O4): Total 0.6% S-series lithium salt (LiSO3F selected): 0.4%; (2) Organic solvents EC: 25% DMC: 20% DEC: 8% EMC: 29.3% (3) Additives: TFPP: 0.2% VC: 2.0% DTD: 0.5%.
[0058] Example 2 To address the needs of electric vehicles in cold winter regions (such as -40℃) for cold start, high current acceleration, and energy recovery, the focus is on optimizing the low-temperature ionic conductivity and rate discharge platform of the electrolyte.
[0059] Formula composition (all percentages by weight): (1) Lithium salts LiPF6: 4.2% LiFSI: 11% B-series lithium salt (LiBF2C2O4 selected): 0.5% S-series lithium salt (LiSO3F selected): 0.3% (2) Organic solvents (quaternary system) EC: 22% DMC: 28% DEC: 0% EMC: 32% (3) Additives TFPP: 0% VC: 1.4% DTD: 0.6%.
[0060] Example 3 To address the need for long-term operation of containerized energy storage systems in high-temperature (60℃) or poorly ventilated environments during summer, the focus is on improving high-temperature cycle life and storage stability.
[0061] Formula composition (all percentages by weight): (1) Lithium salts LiPF6: 6.5% LiFSI: 7% Lithium salt B (LiB(C2O4)2, i.e., LiBOB) is selected: 0.9% S-series lithium salt (Li₂SO₄ selected): 0.3% (2) Organic solvents: EC: 28% DMC: 12% DEC: 18% EMC: 23.3% (3) Additives: TFPP: 0.3% VC: 2.8% DTD: 0.9%.
[0062] For the mass percentages of each component in the other embodiments and comparative examples, please refer to Table 1.
[0063] Table 1
[0064] The electrolytes from the examples and comparative examples were assembled into batteries in the following manner: Positive electrode preparation: The positive active material lithium iron phosphate, the binder polyvinylidene fluoride, and the conductive agent (conductive carbon black and carbon nanotubes) are mixed with the solvent N-methylpyrrolidone (NMP) in a mass ratio of 90:5:5 to form a slurry. The slurry is uniformly coated on a 16μm thick aluminum foil current collector, and after drying, rolling and cutting, the positive electrode is obtained.
[0065] Negative electrode preparation: The negative electrode active material artificial graphite, the binder styrene-butadiene rubber (SBR), the thickener sodium carboxymethyl cellulose (CMC) and the conductive agent Super P are mixed in a mass ratio of 95:2:2:1. Deionized water is added as a solvent and stirred to form a slurry with a solid content of 55%. The slurry is uniformly coated on a 6μm thick copper foil current collector. After drying, rolling and slitting, the negative electrode is obtained.
[0066] Separator: A 12μm thick three-layer composite separator made of polypropylene / polyethylene / polypropylene (PP / PE / PP) is selected.
[0067] Battery assembly: The above-mentioned positive electrode, negative electrode and separator are stacked to form a cell. The cell is then placed in an aluminum-plastic film shell, sealed from the top and side, and vacuum baked at 85°C for 24 hours. The electrolyte prepared above is then injected, and after formation, aging and capacity testing, a lithium-ion battery is obtained.
[0068] The batteries from the above embodiments and comparative examples were subjected to the following tests: 1. -20℃ 50%SOC 20C 10s discharge voltage platform test: In a -20℃ environment, the battery is charged to 50%SOC at 1C constant current and constant voltage. After standing for 4 hours, it is discharged at 20C rate for 10s constant current and the voltage value at the end of the discharge is recorded.
[0069] 2. 60℃ 3C / 3C@80%SOH cycle life test: a. At 25℃, charge the battery at a constant current and constant voltage of 1C to 3.65V / 0.05C cutoff, and let it stand for 15 minutes; b. Let the battery stand at 60°C for 6 hours; c. At 60℃, discharge the battery at a constant current of 3C to 2.5V and let it stand for 10 minutes; d. At 60℃, charge the battery at a constant current but not constant voltage of 3C until it reaches 3.65V cutoff, and let it stand for 10 minutes; e. Repeat steps c) to d) until the capacity retention rate is below 80% and then terminate the test.
[0070] 3. 28-day capacity retention test at 60℃ and 95% SOC: a. Adjust the battery to 95% SOC (capacity cutoff) at 1 / 3C current at room temperature. b. The battery was stored at 60°C. At fixed intervals (7 days, 14 days, and 28 days of storage), the battery was removed and left at room temperature for 6 hours for intermediate testing (open circuit voltage, internal resistance, and room temperature capacity were recorded). The battery was then adjusted to 95% SOC and stored for the next cycle, repeating this process until the 28-day storage period was completed. The test results are shown in Table 2.
[0071] The cycle performance test graphs of the batteries in Examples 1-3 and Comparative Examples 1-2 at 60°C 3C / 3C are shown below. Figure 1 As shown, it can be seen that the high-temperature cycling performance of Examples 1-3 of this application is significantly better than that of Comparative Examples 1-2.
[0072] Table 2
[0073] As shown in Table 1, the electrolytes of Examples 1-7 of this application exhibit low conductivity at -40℃, long cycle counts at 60℃ 3C / 3C @80%SOH, and high capacity retention after 28 days of storage at 60℃ 95%SOC. This indicates that the electrolytes of the present invention can balance the high and low temperature performance of lithium-ion batteries. Comparative Examples 1-2, however, cannot simultaneously achieve the above performance, demonstrating that the synergistic combination of B-series lithium salts and S-series lithium salts with other components in the electrolytes of this invention achieves a balance and uniformity in both high and low temperature performance.
[0074] The specific embodiments of the present invention described above do not constitute a limitation on the scope of protection of the present invention. Any other corresponding changes and modifications made in accordance with the technical concept of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. An electrolyte, characterized in that, The electrolyte includes lithium salt, organic solvent, and additives. The lithium salts include lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, B-series lithium salts, and S-series lithium salts, wherein the chemical formula of the B-series lithium salt is LiBF. n1 X m1 The chemical formula of the S-series lithium salt is Li. x SO n2 F m2 Where X includes one or more of oxalate, sulfate, and catechol, n1=0~4, m1=0~2, x=1~2, n2=2~4, m2=0~1; The organic solvents include ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate; The additives include vinylene carbonate.
2. The electrolyte according to claim 1, characterized in that, Based on the total mass of the electrolyte, the mass percentage of each component in the lithium salt is as follows: lithium hexafluorophosphate 3.5%~9%, lithium difluorosulfonyl imide 5%~13%, B-series lithium salt 0.1%~1.0%, and S-series lithium salt 0.1%~1.0%.
3. The electrolyte according to claim 1, characterized in that, The B-series lithium salts include one or more of LiBF2C2O4, LiBF2SO4, LiB(C2O4)2, LiBF4, LiBF2(C6H4O2), LiB(C6H4O2)2, and LiB(C2O4)(C6H4O2); and / or, The S-series lithium salts include one or more of LiSO3F, LiSO2F, Li2SO4, and Li2SO3.
4. The electrolyte according to claim 1, characterized in that, Based on the total mass of the electrolyte, the mass percentage of each component in the organic solvent is as follows: ethylene carbonate 20%~30%, dimethyl carbonate 10%~30%, diethyl carbonate 0%~20%, and methyl ethyl carbonate 15%~35%.
5. The electrolyte according to claim 1, characterized in that, Based on the total mass of the electrolyte, the mass percentage of each component in the additive is: trifluorophenylphosphine 0%~0.5%, vinylene carbonate 0.5%~3%, and vinyl sulfate 0%~1%.
6. The electrolyte according to any one of claims 1 to 5, characterized in that, Based on the total mass of the electrolyte, the mass percentage of each component is as follows: Lithium hexafluorophosphate 4.5%~5.5%, lithium difluorosulfonyl imide 8.0%~10.0%, B-series lithium salts 0.4%~0.8%, S-series lithium salts 0.2%~0.5%; Ethylene carbonate 23%~27%, dimethyl carbonate 18%~22%, diethyl carbonate 6%~10%, methyl ethyl carbonate 23%~27%; Trifluorophenylphosphine 0.15%~0.35%, vinylene carbonate 1.5%~2.5%, vinyl sulfate 0.3%~0.7%.
7. The electrolyte according to any one of claims 1 to 5, characterized in that, Based on the total mass of the electrolyte, the mass percentage of each component is as follows: Lithium hexafluorophosphate 3.8%~4.6%, lithium difluorosulfonyl imide 10%~12%, B-series lithium salts 0.3%~0.7%, S-series lithium salts 0.2%~0.6%; Ethylene carbonate 20%~24%, dimethyl carbonate 26%~30%, diethyl carbonate 0%~5%, methyl ethyl carbonate 30%~34%; Trifluorophenylphosphine 0%~0.2%, vinylene carbonate 1.0%~2.0%, vinyl sulfate 0.4%~0.8%.
8. The electrolyte according to any one of claims 1 to 5, characterized in that, Based on the total mass of the electrolyte, the mass percentage of each component is as follows: Lithium hexafluorophosphate 6.0%~7.0%, lithium difluorosulfonyl imide 6.0%~8.0%, B-series lithium salts 0.7%~1.0%, S-series lithium salts 0.1%~0.5%; Ethylene carbonate 26%~30%, dimethyl carbonate 10%~14%, diethyl carbonate 16%~20%, methyl ethyl carbonate 16%~20%; Trifluorophenylphosphine 0.2%~0.4%, vinylene carbonate 2.5%~3%, vinyl sulfate 0.7%~1%.
9. A battery, characterized in that, The battery comprises the electrolyte according to any one of claims 1 to 8.
10. The battery according to claim 9, characterized in that, The battery includes a positive electrode sheet, which comprises a lithium iron phosphate-based positive electrode active material; and / or, The battery includes a negative electrode sheet, which includes a graphite-based negative electrode active material.
